Gene Pyramiding for Brown Planthopper Resistance-related Traits, Early Maturity and Aroma of Rice Assisted by Molecular and Phenotypic Markers - Carsono, Nono; Utami, Riski Gusri; Sari, Santika; Wicaksana, Noladhi (AGROSAINSTEK: Jurnal Ilmu dan Teknologi Pertanian, 2020)
The brown planthopper (BPH)-resistant rice, early maturity, and aromatic are expected by both farmers and consumers. The traits have been combined through gene pyramiding and some promising rice genotypes obtained. However the genetic control of BPH resistance and maturity is quantitatively inherited, it is therefore both molecular and phenotypic assessments would be tremendously helpful in selecting promising genotypes. The study aimed to obtain genotypes with such valuable traits. Rice lines were analyzed using molecular markers i.e., RM586, RM589, RM8213 (BPH resistant gene markers); RM7610 and RM19414 (early maturity markers), and IFAP (Internal Fragrant Antisense Primer) for detecting aromatic, and INSP (Internal Non-fragrant Sense Primer) for non-aromatic rice. Phenotypic assessment was performed for brown planthopper resistant-related traits, such as chlorophyll content, stomatal conductance, and trichome density. Other evaluations were heading date and aroma (using 1.7% KOH solution). Results showed that molecular markers for evaluating BPH resistance genes (Bph3, Bph4, Qbph4, and Bph17), aroma (fgr gene), and heading date (Hd2 and Hd3 genes) could differentiate genotypes, and they serve as perfect markers, except for heading date markers. Seven genotypes i.e., #2, #3, #4, #5, #6, #10, and #11 were related to all traits expected based on molecular marker analysis. Meanwhile, genotypes #1, #2, #4, #6, and #11 were similar to their parents based on phenotypic analysis. Pyramiding program based on molecular and phenotypic markers enables us to combine three valuable traits into one rice genotype as presented in this study